2002
DOI: 10.2209/tdcpublication.43.231
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein of Mycoplasma salivarium and Mycoplasma orale strains isolated from HIV-seropositive patients.

Abstract: It has been suggested that infection by some mycoplasma species can act as possible cofactors in the acceleration of immunodeficiency in HIV-infected patients. The present study was designed to examine infections by oral mycoplasma species in HIV-seropositive (HIV(‫))ם‬ patients. Mycoplasma salivarium and Mycoplasma orale were isolated from 59.5% and 16.7% of 42 HIV(‫)ם‬ patients, respectively. Non-M. salivarium and non-M. orale species were isolated from 40.5% of saliva samples from the HIV(‫)ם‬ group and 20.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
(31 reference statements)
0
6
0
1
Order By: Relevance
“…Among patients with HIV/AIDS, co-infection with Mycoplasma spp. is associated with faster progression of a disease which is characterised by immune failure, 12 although the causative relationship remains controversial 21 22 and the Mycoplasma spp. implicated are those more commonly associated with the genitourinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with HIV/AIDS, co-infection with Mycoplasma spp. is associated with faster progression of a disease which is characterised by immune failure, 12 although the causative relationship remains controversial 21 22 and the Mycoplasma spp. implicated are those more commonly associated with the genitourinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that oral Mycoplasma species isolated from HIV‐seropositive patients did not produce superantigen (2). It is possible that some culture conditions or stages affect superantigen production.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that many oral bacterial species isolated from patients with Behcet's disease produce HSP70. We have previously reported that strains isolated from patients with chronic periodontitis with pustulosis palmaris et plantaris (PPP), and HIV‐seropositivity, produce HSPs (1, 2, 11). We have also examined the relationships between the onset of PPP, periodontitis and HSP levels of IgG against HSPs, including A. actinomycetemcomitans DnaJ, in sera (11).…”
Section: Discussionmentioning
confidence: 99%
“…Mycoplasma sp. is also found in the normal flora in oral cavity (Watanabe et al, 1986 ), and certain species such as M. salivarium were reported to cause serious infections in HIV-positive patients (Chattin-Kacouris et al, 2002 ). Actinomyces odontolyticus might cause pulmonary actinomycosis, septicemia, and pulmonary abscesses (Rajesh et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%